Bezier曲線のaffine不変性

affine不変

affine写像 \(\Phi: \mathcal{R}^l \rightarrow \mathcal{R}^n\)

\[ \mathbf{b} = \sum_{i=0}^n c_i \mathbf{b}_i, ~~ \sum_{i=0}^n c_i = 1 \tag{1} \]

に対して

\[ \Phi(\mathbf{b}) = \sum_{i=0}^n c_i \Phi(\mathbf{b}_i) \tag{2} \]

が成立する.

証明)

線形写像: \(F: \mathcal{R}^l \rightarrow \mathcal{R}^n\),平行移動\(\mathbf{v} \in \mathcal{R}^n\)とすると

affine写像 \(\Phi: \mathcal{R}^l \rightarrow \mathcal{R}^n\)は次式のように書ける.

\[ \Phi(\mathbf{x}) = F(\mathbf{x}) + \mathbf{v} \tag{3} \]

\[\begin{eqnarray} \Phi(\mathbf{b}) & = & \Phi \left(\sum_{i=0}^n c_i \mathbf{b}_i \right) \\ & = & F \left(\sum_{i=0}^n c_i \mathbf{b}_i \right) + \mathbf{v} ~~~~~ ...... \text{線形写像の加法性,斉次性から}\\ & = & \sum_{i=0}^n c_i F(\mathbf{b}_i) + 1 \cdot \mathbf{v} \\ & = & \sum_{i=0}^n c_i F(\mathbf{b}_i) + \left(\sum_{i=0}^n c_i \right) \cdot \mathbf{v} ~~~~~ ...... \text{式(1)から}\\ & = & \sum_{i=0}^n c_i \left\{ F(\mathbf{b}_i) + \mathbf{v} \right\} \\ & = & \sum_{i=0}^n c_i \Phi(\mathbf{b}_i) \tag{4} \end{eqnarray}\]

線形写像

加法性: \(F(\mathbf{x} + \mathbf{y}) = F(\mathbf{x}) + F(\mathbf{y})\)

斉次性: \(F(c\mathbf{x}) = cF(\mathbf{x})\)

Bezier曲線

\(\mathbf{P}(t) = \sum_{i=0}^n \mathbf{P}_i B_i^n (t)\) かつ \(\sum_{i=0}^n B_i^n (t) = 1\)

\[ \Phi(\mathbf{P}(t)) = \sum_{i=0}^n \Phi(\mathbf{P}_i) B_i^n (t) \tag{5} \]

が成立


rocky@inf.uec.ac.jp